Cyberlaw: Problem dan Prospek Pengaturan Aktivitas Internet - Nandang Sutrisno (Fakultas Hukum Universitas Islam Indonesia, 2001)
The development of internet, undeniably, has multidimensional implications and specific characters of cyberspace. In fact, mostexisting laws have been provided and created for there alworld. There fore, the questions are whe therornot the laws for realworld provide for cyberspace? Should laws for cyberspace differ from those for realworld? Is it a must to have a specific Cyberlaw? This writing proposes to elaborate on problems a rising or potentially a rising from activities in intemet, especially those related to E-Commerce,directly or indirectly. This paper also tries for ecommend some anticipative alternatives.